Indonesia’s Presidency On G20 2022: Unpacking Its Digital Economic Diplomacy In Advancing Indonesian MSMES Digital Economic Transformation - Abdul Razaq Cangara; Bama Andika Putra; Patrice Lumumba; Chantika Salsabila Alarsah; Andi Faradilla Ayu Lestari (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
After a long period of membership in the Premier global forum of G20, Indonesia has taken the lead in the G20 Presidency 2022. With a theme of "Recover Together, Recover Stronger" to encounter the multi-spectrum repercussion of the Covid-19 Pandemic, Indonesia set out three main agendas of deliberation within, encompassing Global Health Architecture (GHA), Digital Economic Transformation (DET) and Energy Transition (ET). This article considers and puts forward the DET agenda, particularly the Micro, Small, and Medium Enterprises (MSMEs) DET, as the main discussion in this article. It assumes DET agenda that could significantly encounter the problem of economic downturn with its following consequences of losses of many jobs and rising unemployment. Therefore, this article scrutinizes how Indonesia's G20 Presidency could elevate its economic diplomacy capacity to achieve its MSMEs' DET interests. For this purpose, this article employs the analytical framework tailored from the integrated perspective of economic diplomacy, digital economy, and digital economic transformation. This article argues that Indonesia's G20 Presidency has advantaged Indonesia by giving more policy and diplomatic room to campaign and mainstream its MSMEs DET interests to multiple stakeholders from all G20 countries. It consequently crystallizes MSMEs DET as both a normative and practical agenda globally in which Indonesia could further entertain its MSMEs DET interest. In such ways, it is expected that Indonesia could recover its economy after the pandemic, particularly with the advancement of its MSME economic environment. This argument is based on the mapping of the G20 events dynamic substantiating MSMEs DET from December to October 2022. Overall, despite Indonesia's MSMEs DET interest achievement in G20 2022, Indonesia still needs to strengthen its economic diplomacy endeavour related to MSMEs DET in the following G20s forums.